Lavender Jack. Volume 1 - Schkade, Dan (Dark Horse Books, 2026)
"The dawn of the 20th century! The City of Gallery is a place of science, diversity, and wealth... but it's also held in the clutches of a corrupt ruling class that's squeezing it for all it's worth. Enter: LAVENDER JACK-a devilish vigilante whose fighting prowess and advanced technology make him a nightmare for Gallery's elites. But they're not about to loosen their grip on the city without a fight. They've got some devils of their own... Dan Schkade's outstanding webcomic comes to print with a beautiful cover and updated interior art for the first season!"-- Provided by publisher.